Mass religious events as opportunities for tourism promotion. An analysis of users' visits to the website of World Youth Day 2016 in Krakow - Narbona, Juan (Church, Communication and Culture, 2018)
Mass religious events are often an unprecedented tourist opportunity. A clear example was the meeting of Pope Francis with more than three million young people in July 2016 in Krakow, on the occasion of the 31st World Youth Day. Although it was a mainly religious event, the experience of past editions (for example, Madrid 2011 and Rio de Janeiro 2013) shows the strong impact of WYD on the local tourism and hospitality industry. The official website of such event becomes an informative point of reference and a crossroads where the needs of the users and the offer of the promoters meet. This study analyzes the official website of the WYD Krakow 2016 as a source to promote religious touristic sites.